2007
DOI: 10.1073/pnas.0707912104
|View full text |Cite
|
Sign up to set email alerts
|

A protein phosphorylation/dephosphorylation network regulates a plant potassium channel

Abstract: Potassium (K ؉ ) is an essential nutrient for plant growth and development. Plants often adapt to low K ؉ conditions by increasing their K ؉ uptake capability. Recent studies have led to the identification of a calcium signaling pathway that enables plants to act in this capacity. Calcium is linked to two calcineurin B-like calcium sensors (CBLs) and a target kinase (CBL-interacting protein kinase 23 or CIPK23) that, in turn, appears to phosphorylate and activate the potassium channel, Arabidopsis K ؉ transpor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
323
1
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 331 publications
(333 citation statements)
references
References 35 publications
6
323
1
3
Order By: Relevance
“…A similar mechanism was also identified in other plant species (for review, see Véry et al, 2014), such as rice (Oryza sativa; Li et al, 2014). Subsequently, a 2C-type protein phosphatase, AIP1, was identified that interacts with and inactivates the AKT1 channel (Lee et al, 2007). Therefore, a phosphorylation/ dephosphorylation regulatory mechanism for the AKT1 channel was proposed (Lee et al, 2007).…”
mentioning
confidence: 78%
See 1 more Smart Citation
“…A similar mechanism was also identified in other plant species (for review, see Véry et al, 2014), such as rice (Oryza sativa; Li et al, 2014). Subsequently, a 2C-type protein phosphatase, AIP1, was identified that interacts with and inactivates the AKT1 channel (Lee et al, 2007). Therefore, a phosphorylation/ dephosphorylation regulatory mechanism for the AKT1 channel was proposed (Lee et al, 2007).…”
mentioning
confidence: 78%
“…Subsequently, a 2C-type protein phosphatase, AIP1, was identified that interacts with and inactivates the AKT1 channel (Lee et al, 2007). Therefore, a phosphorylation/ dephosphorylation regulatory mechanism for the AKT1 channel was proposed (Lee et al, 2007). In addition, the Ca 2+ -binding protein CBL10 interacts directly with AKT1 and negatively modulates AKT1 activity by competing with CIPK23 to bind AKT1 .…”
mentioning
confidence: 99%
“…CIPKs include an N-terminal kinase catalytic domain followed by a characteristic self-inhibitory motif known as FISL or NAF motif (hereinafter NAF, Pfam no. PF03822) (1, 6) and a protein phosphatase 2C binding domain designated as PPI (11,18,19). The NAF motif directly interacts with the catalytic domain and inhibits the kinase activity.…”
mentioning
confidence: 99%
“…The ankyrin domain, which is present in AKT2 but not in KAT1, is proposed to be important for the interaction of the channel with kinases. 29 Insertion of this domain possibly resulted in a distortion of the proper interaction between cNBD and K HA /K T and in the aberration of functional channel assembly in S. cerevisiae and oocytes.…”
Section: Discussionmentioning
confidence: 99%